Valuation Responses to Random Changes in Perceived Risk: The Impact of Terrorism on the Defence Sector. Issue 1 (2nd January 2022) - Fraser, Jamie; Carbonnier, Gilles
ABSTRACT: This study explores the impact of random changes in risk perceptions that occur as a result of terrorist attacks by examining abnormal variations in defence sector valuations. Using a market model event study methodology, the market impacts of three different sets of terror events are measured: Mass casualty events, events that occur in OECD countries, and events that occur in BRICS countries. The findings are tested against a series of explanatory variables that capture characteristics of the domestic defence sector for 21 country-level sector indices and characteristics of the event itself. Results demonstrate that the response of the defence sector to terror events depends more on event characteristics than economic characteristics, contrary to much of the prevalent literature. We also find that speculation in the defence sector persists for several days following an attack indicating that investors broadly expect a military response, particularly in the case of mass casualty events.